2003
DOI: 10.1093/ps/82.9.1415
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between cholecalciferol and 25-OH-cholecalciferol on performance and eggshell quality of hens fed different levels of calcium and phosphorus

Abstract: Two experiments were conducted to determine whether the presence of 25-OH-cholecalciferol (25-OH-D3) as compared to vitamin D3 produces any beneficial effect on shell quality of laying hens. Experiment 1 consisted of a 4 x 2 factorial arrangement of the treatments with four determined Ca levels (3.34, 4.3, 4.73, and 4.94%) and two sources of vitamin D (vitamin D3 and 25-OH-D3, which were used at 69 microg/kg diet or 2,760 IU/kg diet). Experiment 2 consisted of a 3 x 2 x 2 factorial arrangement of the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 20 publications
3
31
3
Order By: Relevance
“…Specific gravity is a measurement, which has the advantage of not destroying the eggs when measuring eggshell quality; however, it is not very accurate when minimal differences are expected. Previous results evaluating supplementation of 25 (OH) D 3 have also demonstrated a limitation in obtaining advantage when eggshell quality was assessed using specific gravity (Roland & Harms, 1976;Keshavarz, 1996;Keshavarz, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Specific gravity is a measurement, which has the advantage of not destroying the eggs when measuring eggshell quality; however, it is not very accurate when minimal differences are expected. Previous results evaluating supplementation of 25 (OH) D 3 have also demonstrated a limitation in obtaining advantage when eggshell quality was assessed using specific gravity (Roland & Harms, 1976;Keshavarz, 1996;Keshavarz, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The opposite results were reported by Carlos and Edwards (1998) and Berry et al (2003) who did not find any significant effect of F on the egg weight. Accordingly, Keshavarz (2003) showed that the presence of F did not have an effect on performance but reduced several indices of shell quality. In addition, Lim et al (2003) recorded a significant interaction between the NPP level and F for egg production.…”
Section: Discussionmentioning
confidence: 97%
“…The negative effect of F observed in the present study could be due to the greater Ca : P ratios (from 7.5 : 1 to 10.5 : 1) in all of the evaluated diets, and F supplementation may have exacerbated this effect by releasing Ca from the phytate complex. Keshavarz (2003) showed that the presence of F reduced several indices of shell quality. On the other hand, 150 FTU of 3-phytase improved the pigmentation of the egg yolk.…”
Section: Discussionmentioning
confidence: 99%